(untitled) (Research, Society and Development, 2022)
The objective of this work was to promote contextualization, to gather technical, normative, and practical information that can contribute to technicians and academics in the area of ​​civil engineering to raise awareness about the importance of adequate studies and projects for the stabilization of slopes. To achieve the objective of this work, an updated review of the subject was chosen, through bibliographical research of the literature. Slopes, in turn, are classified as the inclined surface of a block of soil or rock. In addition, they can be natural, slopes or cases of slopes, natural or artificial, embankments or cut slopes. Three factors act simultaneously to give stability to a slope or slope: its geometry, its geological properties, and the environmental conditions of the territory where it is located. Vegetation has important importance for the stability of slopes to be protected since the removal of the vegetation itself can cause risk areas. Among these risks are erosions that are classified as erosion by raindrop collision (splash), laminar or sheet erosion, linear erosion, or concentrated flow. The use of slopes covered with vegetation has been an important means of avoiding surface erosion, being considered a prevention technique, where grass planting is a low-cost and easy-to-perform technique. Thus, the vegetation favors the constancy of the soil, especially due to the increase in shear strength due to the contribution offered by the roots.